An Investigative Study on the Learning Difficulties in Mathematics Encountered by Primary 4 Children: In Search of a Cognitive Equation for Mathematics Learning - Chia, Noel Kok Hwee; Peng Kho, Chiew (Journal of the American Academy of Special Education Professionals, 2011)
This study investigated how the five components – vocabulary, computation, general information, problem story, and attitude toward mathematics (subtests of the standardized Test of Mathematical Abilities-Second Edition) – are involved in mathematics learning of 40 randomly selected Primary 4 Singaporean children, who have been failing in their mathematics class tests and school examinations since Primary 3. The authors have attempted to formulate a cognitive equation for mathematics learning in order to explain the underlying causes of failure in mathematics learning and also to inform mathematics teachers what they ought to know and how best they could go about helping these children.